2015
DOI: 10.1021/acs.chemmater.5b01522
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of CdSe Quantum Dots by Graphene and MoS2 Monolayer Encapsulation

Abstract: The encapsulation of a monolayer of CdSe quantum dots (QDs) by one-to-three layer graphene and MoS 2 sheets protects the QDs from oxidation. Photoluminescence (PL) from the QD cores shows a much slower decrease in core diameter over time due to slower oxidation in regions where the QDs are covered by van der Waals (vdW) layers than in those where they are not, both for chips stored in the dark and in the presence of light. PL mapping shows that the CdSe QDs under the central part of the vdW sheet age slower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…MoS 2 shows good stability in air at room temperature. A few experiments and theoretical calculations have demonstrated that MoS 2 could be used as a passivation or protection layer to prevent oxidation of other materials . Oxidation of MoS 2 occurs at temperature higher than 300°C in air.…”
Section: Molybdenum Disulfidementioning
confidence: 99%
“…MoS 2 shows good stability in air at room temperature. A few experiments and theoretical calculations have demonstrated that MoS 2 could be used as a passivation or protection layer to prevent oxidation of other materials . Oxidation of MoS 2 occurs at temperature higher than 300°C in air.…”
Section: Molybdenum Disulfidementioning
confidence: 99%
“…At these loadings (below percolation as per Fig. 3), 2D sheets of few-layered graphene serve as excellent waterimpermeable 25 and unreactive barriers and greatly reduce the concentration of microscopic defects and pores within the polymeric matrix. As such, the graphene inclusions substantially increase the effective pathlengths for the diffusion of water and aggressive species towards the metal surface.…”
Section: Sce) Time (Days)mentioning
confidence: 99%
“…[22][23][24] An alternative strand of research has focused on the corrosion protection endowed by graphene nanocomposites wherein few-layered chemically derived graphene flakes are incorporated within a polymeric matrix. As an impermeable 2D material, 25 inclusion of graphene adds substantial tortuosity to pathways for diffusion of species participating in the redox reactions of corrosion. Functionalization of graphene and/or incorporation of graphene in nonconductive polymers results in a considerable enhancement of the tortuosity of ion diffusion pathways and a substantially increased pore transport resistance while preventing direct electrochemical coupling with the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…For NPs capped by ligands with nonpolar ends, this means that the upper solvent needs to be more nonpolar and the lower one more polar. (2) The solvents must be immiscible, so they do not mix. (3) The upper solvent must be less dense, so it does not displace the lower solvent.…”
Section: ■ Introductionmentioning
confidence: 99%